2005
DOI: 10.1002/hbm.20137
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum and auditory function: An ALE meta‐analysis of functional neuroimaging studies

Abstract: Abstract:Over the past two decades neuroimaging data have accumulated showing that the cerebellum, traditionally viewed only as a motor structure, is also active in a wide variety of sensory and cognitive tasks. We have proposed that instead of explicit involvement in any particular motor, sensory, or cognitive task, the cerebellum performs a much more fundamental computation involving the active acquisition of sensory data. We carried out an activation likelihood estimate (ALE) meta-analysis to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(195 citation statements)
references
References 111 publications
(128 reference statements)
16
175
2
2
Order By: Relevance
“…Finally, extensive activation was seen in right lateralized crus I and II in posterior cerebellum. Recent evidence suggests that the latter regions support aspects of verbal working memory or phonological encoding (25). (Similar results are obtained when valid and invalid trials are analyzed separately; see SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 70%
“…Finally, extensive activation was seen in right lateralized crus I and II in posterior cerebellum. Recent evidence suggests that the latter regions support aspects of verbal working memory or phonological encoding (25). (Similar results are obtained when valid and invalid trials are analyzed separately; see SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 70%
“…The coordinates of the reported cerebellum activation (i.e., -19 -41 -20 for weaker musical relations (Tillmann et al, 2003), and -32 -57 -23 for the same musical relations 1 ) were close to those reported in an activation likelihood estimate meta-analysis for a wide range of auditory tasks (-44 -50 -32 (crus I) and -20 -50 -22 (lobule V) (Petacchi et al, 2005)). Beyond being part of a network supporting increased auditory processing, the increased cerebellar activation might be linked to a cerebellar role in generating musical expectations based on knowledge of prototypical sequences and association strengths in music.…”
Section: Nih Public Accesssupporting
confidence: 73%
“…A seminal fMRI paper by Gao et al (1996) reported that the dentate nuclei of the cerebellum were more active during manual tasks that emphasized sensory discrimination, rather than during movement per se. Neuroimaging studies have shown increased activation of the cerebellum during auditory tasks (Petacchi et al, 2005), such as frequency, intensity and duration discrimination (Belin et al, 2002), the processing of complex nonspeech sounds over pure tones (Vouloumanos et al, 2001), as well as for auditory attention (Janata, Tillmann, & Bharucha, 2002) and the perception of musical structures (Parsons, 2001;Tillmann, Janata, & Bharucha, 2003). Work in auditory perception is just one piece of a larger emerging picture that suggests potential cerebellar contributions to higher cognitive functions involving memory and language (see Fiez, 1996;Justus & Ivry, 2001 for reviews).…”
mentioning
confidence: 99%
“…Though one possibility is that the pathophysiological mechanism underlying these lesions was crossed cerebellocerebral diaschisis (e.g., Cook et al, 2004), it is equally possible that they reflect ipsilateral cerebellar cerebral diaschisis, implying that the cerebellum might be bilaterally involved in language processing (Murdoch & Whelan, 2007). Another exception to the lateralization of linguistic function is to be found in prosodic and auditory language processing, that both seem to be left lateralized within the cerebellum (e.g., Callan et al, 2007;Petacchi et al, 2005).…”
Section: Functional Topography Of the Cerebellummentioning
confidence: 99%